Distribution of Snail Mucous Extract (Achatina Fulica) on the Number of Wound’s Basal Epithelial Cells in Rats of Wistar Strain - Dina Karimah Putri1 , Titiek Berniyanti 2, Edhi Jularso 3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Acharan sulfate, a new glycosaminoglycan isolated from Achatina fulica, obtained from Kediri,East Java, Indonesia, plays a big role in wound healing process, because it can promote re-epithelialization.Purpose: This study aims to prove that extract of Achatina fulica mucous will increase the number of basalepithelial cells of the wound incision in the back of white male rats of wistar strain. Method: This researchwas done by an in-vivo experimental laboratory, using 14 white male rats of wistar strain that given anincision injury in the back with a length of ± 2 cm and depth of ± 2 mm. They were divided into two treatmentgroups, that are control group which is the incision wounds were given saline solutions; and treatment groupwhich is the incision wounds were given an extract of Achatina fulica mucous with crude acharan sulfatelevel is 86,74%. This treatment is given 3 ml once a day for five days. On the sixth day, biopsy was carriedout to make a histological specimen, then evaluate under a microscope to account the number of basalepithelial cells of the wound incision. Then statistical analysis was conducted by using independent samplest-test with ?=0,05. Results: There were significant differences between two treatment group, that are thenumber of basal epithelial cells in control group and treatment group (p<0,05). Conclusion: Extract ofAchatina fulica mucous with crude acharan sulfate level is 86,74% increase the number of basal epithelialcells of the wound incision in the back of white male rats of wistar strain.